PENGGUNAAN FAN TYPE HOLOGRAM DENGAN SOLAR CELL SEBAGAI PILIHAN ALTERNATIF BILLBOARD DI KOTA AMBON - Eka Rahmat Mahayani Anthonio Putera Lilipaly; Eka Adhitya Dharmawan (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) Politeknik Negeri Ambon, 2021)
This research aimed to investigate the use of fan type hologram, that is considered to be a new technology, to replace conventional billboard. Billboard usage consumes plenty of energy and is not flexible. Fan type hologram is expected to reduce the electricity use and becomes more attractive to the general society. Prototype of the system build with solar cell as the source of energy, and battery as the storage. The energy from the sun is also measured to confirmed the energy supply is enough.The experiment showed that the initial cost for billboard is less expensive than the fan type hologram. On the other hand, the use of electricity of fan type hologram is much less than the billboard. It is also does not pay the monthly electricity bill, while conventional billboard needs to pay around Rp.252.000,- per month. 91.2% respondents agree for the replacement of the conventional billboard with fan type hologram.